This study explores the role of digital literacy in promoting social inclusion within marginalized communities. By investigating access to technology, digital education programs, and online social networks, the research assesses how digital skills can imp - Emily Johnson; Michael Lee; Rachel Brooks (International Journal of Humanities and Social Sciences Reviews, 2024)
This study explores the role of digital literacy in promoting social inclusion within marginalized communities. By investigating access to technology, digital education programs, and online social networks, the research assesses how digital skills can improve participation in social, economic, and political spheres. Findings indicate that digital literacy significantly enhances opportunities for social inclusion, though challenges such as access and affordability remain significant barriers.